Investigation on the Vibration Effect of Shock Wave in Rock Burst by In Situ Microseismic Monitoring - Mingshi Gao; Hongchao Zhao; Yichao Zhao; Xiaojun Gao; Xiangyu Wang (Shock and Vibration)
Rock burst is a physical explosion associated with enormous damage at a short time. Due to the complicity of mechanics of rock burst in coal mine roadway, the direct use of traditional investigation method applied in tunnel is inappropriate since the components of surrounding rock are much more complex in underground than that of tunnel. In addition, the reliability of the results obtained through these methods (i.e., physical simulation, theoretical analysis, and monitoring in filed application) is still not certain with complex geological conditions. Against this background, present experimental study was first ever conducted at initial site to evaluate the effect of shock wave during the rock burst. TDS-6 microseismic monitoring system was set up in situ to evaluate the propagation of shock wave resulting in microexplosions of roadway surrounding rock. Various parameters including the distance of epicentre and the characteristic of response have been investigated. Detailed test results revealed that (1) the shock wave attenuated exponentially with the increase of the distance to seismic source according to the equation of E=E0e-ηl; particularly, the amplitude decreased significantly after being 20 m apart from explosive resource and then became very weak after being 30 m apart from the seismic source; (2) the response mechanics are characteristic with large scatter based on the real location of surrounding rock despite being at the same section. That is, the surrounding rock of floor experienced serious damage, followed by ribs, the roof, and the humeral angles. This in situ experimental study also demonstrated that microseismic monitoring system can be effectively used in rock burst through careful setup and data investigation. The proposed in situ monitoring method has provided a new way to predict rock burst due to its simple instalment procedure associated with direct and reasonable experimental results.